2014
DOI: 10.3390/molecules19056294
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Four Different Analytical Tools to Determine the Regional Origin of Gastrodia elata and Rehmannia glutinosa on the Basis of Metabolomics Study

Abstract: Chemical profiles of medicinal plants could be dissimilar depending on the cultivation environments, which may influence their therapeutic efficacy. Accordingly, the regional origin of the medicinal plants should be authenticated for correct evaluation of their medicinal and market values. Metabolomics has been found very useful for OPEN ACCESSMolecules 2014, 19 6295 discriminating the origin of many plants. Choosing the adequate analytical tool can be an essential procedure because different chemical profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…By searching previous literatures, we found that the studies of Lee and Zuo were similar to ours. However, these three studies were not completely consistent.…”
Section: Resultssupporting
confidence: 72%
“…By searching previous literatures, we found that the studies of Lee and Zuo were similar to ours. However, these three studies were not completely consistent.…”
Section: Resultssupporting
confidence: 72%
“…Currently, the approaches for detecting the origin of G. elata are mainly sensory analysis and analytical methods. The former depends basically on the experience and personal emotion of G. elata , which is not objective and lacks scientific understanding; the latter is restricted to the detection of a few active components using methods such as HPLC(LC-MS), GC(GC-MS) and capillary electrophoresis [ 7 , 8 , 9 ], which are often labor-intensive, expensive, time-consuming and require large amounts of organic solvent. In the end, the quality value of the tested sample is determined as “qualified” or “unqualified” according to the presenting acceptance criteria [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been recorded in ancient China, and its dry tubers are commonly used as medicine (Chinese Pharmacopoeia Commission, 2015). It is currently planted in East Asian nations (e.g., China, Japan, South Korea, and India) (Lee et al, 2014). G. elata is largely adopted to treat dizziness, cancer, depression, epilepsy, convulsion, inflammation, liver protection, anti-aging, neuroprotection, and other diseases (Chen J. et al, 2016;Chen L. et al, 2016;Zhan et al, 2016;Kim et al, 2017;Lin et al, 2018;Wang et al, 2018;Zhang et al, 2018;Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%